FACTORS INFLUENCING MENTAL AND PSYCHOLOGICAL HEALTH DURING PREGNANCY - SHARANOOR HUSSAIN (The Journal of Research ANGRAU, 2023)
The study aimed to evaluate maternal mental and psychological health throughout the pregnancy based on age, religion, and occupation. In this cross-sectional study, a total of 66 pregnant women from govt. and private hospitals in Coimbatore city who were admitted between December 2019 and January 2020 were selected as respondents.Purposive sampling method was applied to select the samples. A self-constructed tool on Pregnancy Psychological Status Scale (which assesses mental health) was developed and used to collect data from pregnant women. Results revealed that significant differences in mental and psychological health based on religion (p=0.005) and occupation (p<0.001). The overall level of psychological status (Mental health) among Hindu pregnant women was found better as compared to Muslims and Christians. Regarding occupation, housewives reported higher mental and psychological health followed by private and government employees. However, no significant differences could be seen among various age groups of pregnant women.